2020
DOI: 10.1016/j.breast.2019.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of breast-conserving treatment for axillary lymph node metastasis from occult breast cancer with negative breast MRI

Abstract: Purpose We conducted this study to investigate the prognosis and failure pattern after breast-conserving treatment (BCT) in patients with occult breast cancer (OBC) with negative breast magnetic resonance imaging (MRI) (MRI-OBC). Materials and methods Survival rates and failure patterns in 66 patients who received axillary lymph node dissection (ALND) and BCT for MRI-OBC between 2001 and 2013 at seven hospitals were analyzed. OBC was defined as adenocarcinoma in the axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…38,39 Patients with a negative MRI who underwent breast conservation treatment instead of mastectomy had 96% breast cancer-free survival in a multicenter study with a small risk of ipsilateral recurrence. 40…”
Section: Indications For Breast Mrimentioning
confidence: 99%
“…38,39 Patients with a negative MRI who underwent breast conservation treatment instead of mastectomy had 96% breast cancer-free survival in a multicenter study with a small risk of ipsilateral recurrence. 40…”
Section: Indications For Breast Mrimentioning
confidence: 99%
“…Also, our limited sample failed to compare the different prognoses of patients with MRI positivity/pathological malignancy to those with MRI negativity. MRI has been playing an increasingly important role in identifying primary occult lesions and predicting therapeutic effects [29,30]. If an occult focus is found via MRI, it should be excluded from the occult neoplasm in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This study was based on data from an era predating routine use of breast MRI during preoperative assessment. Recent studies specifically evaluating MRI-negative OBC have also demonstrated no differences in survival outcomes between these therapeutic approaches [14]. Accordingly, the consensus of the MTB discussion after obtaining the additional genomic studies was that BCT with RT was sufficient for local management of the primary tumor and suspected second OBC.…”
Section: Molecular Tumor Boardmentioning
confidence: 99%